Stress analysis of the various dimensions of the spring - Zajalara, Mat Lazi (2012)
This report deals with propose of new dimension of the spring to the suspension system. The objective of this project is to analyze the effect of the spring performance when we modified the dimension of the spring. The new design of the spring will be drawn by using SolidWorks® software. Then this a few dimension of the spring will be testing by using MSC. Nastran/Patran software. This software was used to analyze the stress on the different dimension of the springs. The stress results of the different dimensions were observed and recorded. The stress values indicated that the one of the new dimension of the spring can withstand the highest stress compared to the other spring.